Pengaruh Penanaman Modal Dalam Negeri dan Penanaman Modal Asing terhadap Pertumbuhan Ekonomi Provinsi Sumatera Barat - Riva Almaheni; Nini Sumarni; Kahdijah Nurani; Novera Martilova (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to understand how the impact of Domestic Investment (PMDN) and Foreign Investment (PMA) affects Economic Growth as seen through the Gross Regional Domestic Product (GRDP) of West Sumatra Province. The methodology applied in this study uses quantitative methods, and the data used was obtained through documentation techniques, specifically secondary data sourced from the Central Statistics Agency (BPS) for the years 1995-2024. The data in this study were processed using SPSS version 21. The analytical techniques used in this study include classical assumption testing, multiple linear regression analysis, determination coefficient testing, and hypothesis testing. Based on the results of this study, it is concluded that PMDN has a positive and significant impact on the economic growth of West Sumatra Province, with a significance value of 0.000 and a t-count > t-table, namely 4.604 > 2.051. Partially, foreign direct investment (PMA) has a positive and significant effect on the economic growth of West Sumatra Province with a significance value of 0.002 and a t calculated > t table, which is 3.416 > 2.051. Together, domestic investment (PMDN) and foreign direct investment (PMA) have a positive and significant effect on the economic growth of West Sumatra Province with a significance value of 0.000 and an f calculated > f table, which is 36.696 > 3.35.